Pengelolaan Kegiatan Sponsorship pada Tahap Pra Pelaksanaan The Indo EBTKE Conex 2018 oleh Quad Event Management - Annisa Fitri; Imam Syafganti (Bisnis Event, 2021)
This study aims to determine the management of sponsorship activities in the pre-implementation stage of The Indo EBTKE Conex 2018 and to find out the obstacles and solutions made. The type of research used is qualitative with the method of data analysis using descriptive analysis. The results of the study concluded that at the pre-stage stage consisted of several personal selling techniques to get sponsors. When offering a sponsor package, Organizer must look at the financial condition of the prospective sponsor's company so that the company can still participate.